1990
DOI: 10.1172/jci114910
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I expression by tumors of neuroectodermal origin with the t(11;22) chromosomal translocation. A potential autocrine growth factor.

Abstract: Expression of insulin-like growth factor I (IGF-I) mRNA by some tumor cell lines of neuroectodermal origin has been described. To further explore the significance of IGF-I mRNA expression in these tumors, a more extensive analysis was performed. Most (9 of 10) neuroectodermal tumor cell lines with a t(11;22) translocation (primitive neuroectodermal tumor IPNETI, Ewing's sarcoma, esthesioneuroblastoma) expressed IGF-I mRNA, whereas 0 of 15 cell lines without the translocation (PNET, neuroblastoma) expressed IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 41 publications
4
114
0
1
Order By: Relevance
“…Most of the EWS tumors carry the t(11;22)(q24;q12) translocation resulting in expression of fused EWS/ FLI-1 protein, including the A4573 cell line used in the present study (Yee et al, 1990;Delattre et al, 1992). The suppression of EWS/FLI-1 transcription using antisense cDNA or dominant-negative constructs resulted in growth inhibition of EWS cells in vitro indicating the involvement of this chimeric oncoprotein in regulation of cell proliferation (Kovar et al, 1996).…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofmentioning
confidence: 82%
“…Most of the EWS tumors carry the t(11;22)(q24;q12) translocation resulting in expression of fused EWS/ FLI-1 protein, including the A4573 cell line used in the present study (Yee et al, 1990;Delattre et al, 1992). The suppression of EWS/FLI-1 transcription using antisense cDNA or dominant-negative constructs resulted in growth inhibition of EWS cells in vitro indicating the involvement of this chimeric oncoprotein in regulation of cell proliferation (Kovar et al, 1996).…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofmentioning
confidence: 82%
“…EWS/ETS aberrant transcription factors could activate the hCRD-BP/IMP-1 gene via the 2 ETS-2 binding sites in the promoter region and the additional one downstream of the transcription-start site. 13 So far, we can only speculate about the biologic role of hCRD-BP/IMP-1 in sarcomas, but previous studies have indicated that these tumors exhibit altered expression of c-myc 14 and IGF-II, 15,16 both of which could promote tumor growth. For example, in osteosarcomas, several of which (6/8) expressed hCRD-BP, upregulated c-myc expression is frequently not associated with gene amplification.…”
Section: C-myc Mrna Levels In Crd-bp/imp-1-negative and -Positive Tummentioning
confidence: 99%
“…16 However, established cell lines containing the t(11;22) translocation of Ewing's or PNET origin do not express IGF-II mRNA. 15 Ectopic expression of hCRD-BP/IMP-1 may result in upregulation of c-myc expression, permitting increased proliferation rates. It is well established that c-myc overexpression alone, although not sufficient to transform cells, perturbs many aspects of cellular physiology that are altered in transformed cells, such as cell growth and metabolism, cell-cycle rate, apoptosis, adhesion and cytoskeletal organization.…”
Section: C-myc Mrna Levels In Crd-bp/imp-1-negative and -Positive Tummentioning
confidence: 99%
“…Several potential autocrine growth factor loops have also been described. The presence of an intact insulin-like growth factor type I receptor (IGFRI) appears to be essential for transformation by EWS ± ETS proteins and this receptor may function in survival and/or mitogenic signaling in ET (Scotlandi et al, 1996;Toretsky et al, 1997;Yee et al, 1990). We have reported that the mammalian homologue of bombesin, gastrin releasing peptide (GRP), functions as an autocrine growth factor in these tumors (Lawlor et al, 1998).…”
Section: Introductionmentioning
confidence: 99%